Periodic fever, aphthous stomatitis, pharyngitis, and adenitis (PFAPA) syndrome: A review. Issue 3 (1st July 2021) - Wang, Alicia; Manthiram, Kalpana; Dedeoglu, Fatma; Licameli, Greg R.
Abstract : Periodic fever, aphthous stomatitis, pharyngitis, and adenitis (PFAPA) syndrome is the most common periodic fever condition in children, with most cases appearing by the age of 5. Although PFAPA is generally a self‐limited condition, it can have a major impact on a child's quality of life, as well as that of their family. Recent research has continued to shed light on the genetic and immunologic factors that play a role in the pathogenesis of PFAPA. There also exists significant heterogeneity in treatment strategies, and progress has been made to develop evidence‐based management strategies and establish a standard of care. This review will outline current knowledge regarding the pathogenesis of PFAPA, as well as treatment strategies and our clinical experience.